Interaction between Neurogenic Pulmonary Edema and Thoracic 3 DRG Degeneration Following Spinal Subarachnoid Hemorrhage: First Experimental Study - Sirinoglu, Deniz; Sarigul, Buse; Kanat, Ayhan; Aydin, Mehmet Dumlu; Demirtas, Rabia (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Neurogenic pulmonary edema (NPE) following subarachnoid hemorrhage (SAH) is still one of the most catastrophic complications with high morbidity and mortality rates. Systemic sympathetic hyperactivity has been considered in the pathogenesis, but it has not been clarified. In this study, we investigate the relationship between the degeneration of the T3 dorsal root ganglion (DRG) and the development of NPE following spinal SAH.Methods The study was conducted on 23 rabbits. Five rabbits were used as the control group, 5 as the sham group (n = 5), and 13 as the study group. The correlation between the degenerated neuronal densities of the T3 nerve axons and neurons in the DRG and NPE scores was analyzed statistically.Results A correlation between the neuronal degeneration of the T3 nerve, its DRG, and high NPE scores was found in the study group and the sham group. Massive NPE was detected in the study group along with neural degeneration of T3 axons and ganglia.Conclusion The present study indicates that NPE and pulmonary artery vasospasm can be prevented by reducing T3 DRG degeneration.
Keywords: DRG; thoracic nerve 3; neurogenic pulmonary edema; spinal subarachnoid hemorrhage